Advancing stroke genetics in Hawai‘i and the Pacific Islands - Brown, Stacy C.; Galang, Christine Anne T.; Kana'iaupuni, Mālialani; Dowsett, Leah; Fox, Keolu; Nakagawa, Kazuma (Frontiers in Stroke, 2023)
Stroke, the second leading cause of death worldwide, has partially heritable risk. Genome-wide association studies (GWAS) of stroke continue to identify increasing genetic risk loci. These discoveries point to novel disease mechanisms and causal risk factors, and herald genetics-based precision medicine strategies. In Hawaiʻi, people of Indigenous communities who identify as Native Hawaiian or Pacific Islanders present with stroke at younger ages and suffer dramatically higher stroke mortality rates compared with other regional populations. This disparity is compounded by relative ancestral underrepresentation in stroke genetics research and, by extension, exclusion from cutting-edge medical opportunities based on genetic discovery. In this article, we discuss the issues contributing to the scientific biases experienced by Indigenous populations in the Pacific Islands, as well as community-based efforts now underway to address them.